Issues to be considered on obtaining plant models for formal verification purposes - Pacheco, R. (2016)
The development of dependable software for mechatronic systems can be a very complex and hard task. For facilitating the obtaining of dependable software for industrial controllers, some powerful software tools and analysis techniques can be used. Mainly, when using simulation and formal verification analysis techniques, it is necessary to develop plant models, in order to describe the plant behavior of those systems. However, developing a plant model implies that designer takes his (or her) decisions concerning granularity and level of abstraction of models; approach to consider for modeling (global or modular); and definition of strategies for simulation and formal verification tasks. This paper intends to highlight some aspects that can be considered for taking into account those decisions. For this purpose, it is presented a case study and there are illustrated and discussed very important aspects concerning above exposed issues.